Bioaccumulation of mercury in shrimp with respect to the concentration in waters and sediments of the Ocoña River (Camaná-Arequipa) - Delgado-Pacheco, Jorge; Acevedo-Obando, Grace; Almirón, Jonathan; Ortiz -Valdivia, Yosheff; Aguilar-Ccuno, Camila; Tupayachy-Quispe, Danny (LACCEI, 2024)
The present study seeks to analyze the relationship between the concentration of mercury in the Ocoña River and the presence of mercury in shrimp. To do this, samples of water, sediment and shrimp were taken in three specific places in the basin: Alto Molino, Secocha and Urasqui. Mercury concentration results were obtained in mg/kg and mg/L. The average mercury values in shrimp were 0.0169, 0.0162 and 0.0151 mg/kg, in sediments they were 0.0474, 0.0471 and 0.0470 mg/kg, and in surface water they were 0.00049, 0.00041 and 0.00038 mg/L for the three locations respectively. The results indicate that the concentration of mercury in shrimp is related to that of sediments, but not to that of surface water in the Ocoña River. This study supports the importance of sediment quality in mercury contamination in shrimp in the Ocoña River basin.